Flood Forecasting using a Transfer Hydrograph Approach - Saihul Anwar (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2010)
This paper describes the development and application of a transfer hydrograph approach to flood forecasting on the Cimanuk River at the city of Jatigede in West Java, Indonesia. The Transfer Hydrograph (TH) is a transfer function that transforms total rainfall into a flood hydrograph at the basin outlet. As opposed to the conventional unit hydrograph approach which uses effective rainfall and direct runoff, the transfer hydrograph uses the total rainfall and the direct runoff at the basin outlet. The Cimanuk river basin (drainage area : 1,442 km2) has four sub basins. It was found to be necessary to further extend the application of the transfer hydrograph concept to include all channel routing effects. This because the rainfall at each subbasin was found to be quite independent of the rainfall at other sub basins, and run off data were only available at the basin outlet at Jatigede. Using the available data, transfer hydrograph were derived for each sub basin and later combined to give the runoff hydrograph at Jatigede. The approach was tested against recorded rainfall-run off data at Jatigede and was found to give very reasonable results. For flows above 300 m3/second, the maximum error of prediction was less than 12 %.